Investigation of the Indian Forest sector’s performance during the last three and half decades - Chaudhry, Pradeep; Tambe, Sandeep (Ecological Questions, 2023)
About seventy years ago, independent India’s first National Forest Policy, 1952 clearly mentioned covering one-third of the country’s geographical area under forest cover, but going by the trend of growth in forest cover during the past three and half decades, it is evident that this target is not going to be fulfilled in the near future. The quality of the country’s forests in terms of average productivity, per capita availability, growing stock, and forest type/composition have also declined during the last 35 years as evident from available research articles/reports through secondary literature survey. A multi-pronged strategy giving more emphasis to agroforestry, adopting an innovative result-based Telangana state afforestation model, creating sustainable green funds by different states, and restoring degraded forest lands by strengthening participatory forest management has been suggested in the paper to achieve forest and tree cover target and for improving forest quality.